1995
DOI: 10.1182/blood.v85.6.1540.bloodjournal8561540
|View full text |Cite
|
Sign up to set email alerts
|

Cord blood T lymphocytes lack constitutive perforin expression in contrast to adult peripheral blood T lymphocytes

Abstract: Perforin is the cytolytic pore-forming protein, which alone can be responsible for the lethal hit in one of the killing mechanisms used by natural killer (NK) cells or cytotoxic T lymphocytes. In this study, perforin expression was investigated in cord blood (CB) lymphocytes to determine their killing potential in vivo. The majority of CB CD3- NK cells had the protein. Compared with adult perforin-positive NK cells, a significantly lower percentage of cells expressing CD56 and CD57, the related neural cell adh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(22 citation statements)
references
References 30 publications
3
19
0
Order By: Relevance
“…Berthou and colleagues found no constitutive expression of perforin in cord blood cd or CD4 + T cells as opposed to adult blood cells, whereas cord blood CD8 + T cells expressed perforin. 25 We therefore conclude that the perforin expressing CD3 + T cells we detected here belong to the CD8 + T cell subset.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Berthou and colleagues found no constitutive expression of perforin in cord blood cd or CD4 + T cells as opposed to adult blood cells, whereas cord blood CD8 + T cells expressed perforin. 25 We therefore conclude that the perforin expressing CD3 + T cells we detected here belong to the CD8 + T cell subset.…”
Section: Discussionsupporting
confidence: 52%
“…Perforin and granzyme B are important effector molecules of cytotoxic T and NK cells that mediate target cell lysis and induction of apoptosis. 25 Expression of these molecules was examined both ex vivo and after non-specific stimulation. Maternal cd and CD3 + T cells expressed both perforin and granzyme B ex vivo but expression by cord cd or CD3 + T cells was minimal (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The immaturity of lymphocytes in CB probably reduces the risk and severity of GVHD [11][12][13][14]. One study has shown that the cytotoxic activity in MLR of CB T cells was minimal [15].…”
Section: Discussionmentioning
confidence: 99%
“…The overwhelming majority of T lymphocytes present in UCB is naïve, shows little baseline cytotoxicity, and exhibits atypical functional properties. Indeed, the T lymphocytes secrete lower levels of IL-2, IL-4, IL-10, and IFN-␥ in vitro and express lower levels of Gr and perforin, molecules that are hallmarks of T H 1 responses [112,113]. Based on their production of high levels of IL-13, UCB T cells also exhibit an antiinflammatory T H 2/Tc2 bias [114].…”
Section: Involvement Of T and Nk Cells In Gvhdmentioning
confidence: 99%